Implementasi Algoritma Pencarian Rute Dijkstra Pada Game Great Elephant dengan Unity Engine - Ahmad Zuhdi; Ryan Aji Wijaya; M. Abu Jihad Plaza R; Nadia Salsabila (Sienna, 2026)
The rapid development of modern game technology drives the urgent need for efficient pathfinding systems and structured development processes. In maze-based games, routing algorithms are highly crucial for regulating Non-Player Character (NPC) movements optimally. This research implements the Dijkstra algorithm for shortest pathfinding on an elephant character in the 2D game "Great Elephant" using the Unity Engine. This study serves as an extension of previous research that implemented the A* algorithm. The game development methodology applies the iterative Game Development Life Cycle (GDLC) framework to ensure a structured production process. Furthermore, software quality testing focuses on the functionality aspect using the ISO 25010 standard through two distinct scenarios: the character's success in reaching the destination and the algorithm's success in finding the shortest route. The test results directly executed within Unity demonstrate that the Dijkstra algorithm successfully navigates the elephant character from the starting coordinates to the destination point optimally. The system accurately evaluates 19 search points and successfully determines the single best shortest route consisting of 7 node points without any obstacles or computational errors. Based on the evaluation of the ISO 25010 functionality criteria, the implementation of the Dijkstra algorithm in the game "Great Elephant" achieves a perfect success rate of 100%.